Short Communication: Investigating environmental impacts of long-term monoculture of sugarcane farming in Indonesia through DPSIR framework - Rivandi Pranandita Putra; Muhammad Rasyid Ridla Ranomahera; Muhammad Syamsu Rizaludin; Rahmad Supriyanto; Vita Ayu Kusuma Dewi (Society for Indonesian Biodiversity, 2020)
Abstract. Putra RP, Ranomahera MRR, Rizaludin MS, Supriyanto R, Dewi VAK. 2020. Short Communication: Investigating the environmental impacts of long-term monoculture of sugarcane farming in Indonesia through DPSIR framework. Biodiversitas 21: 4945-4958. An increasing trend of sugar demand in Indonesia due to the rising population has forced the government to boost its national sugarcane production through intensification program. Long-term monoculture system has long been practiced by sugarcane growers in Indonesia, particularly by large sugar companies for more than 30 years. This farming method bolsters the government’s program in scaling-up national sugar production. Through a literature study, the present study analyzed the impacts of long-term sugarcane monoculture in Indonesia on agroecosystem functions by using the Driver-Pressure-State-Impact-Response (DPSIR) framework. Results showed that long-term sugarcane monoculture leads to decreased soil quality, lowered hydrological functions, reduced agrobiodiversity, and increased greenhouse gas emissions. Those conditions corresponded to reduced sugarcane yield and productivity, increased pests and diseases, decreased income gained by growers, higher dependencies on chemicals, and higher cultivation costs. In the end, we proposed several sustainable crop management to mitigate the detrimental effects of sugarcane monoculture practice in Indonesia. These include performing crop break or rotation with legume or the other cash crop, intercropping, green harvesting and trash blanket, precision agriculture methods, and soil amendment with organic matters. However, some constraints in implementing those sustainable crop management, such as inadequate knowledge and capital, should be considered. The information given in this study can be used by sugarcane growers or companies, policymakers, and sugarcane-related stakeholders as considerations to improve sugarcane productivity while at the same time minimizing its impact on the environment.